NOAfaults: a digital database for active faults in Greece - Ganas, A.; Oikonomou, I. A.; Tsimi, C. (Bulletin of the Geological Society of Greece, 2013)
This paper documents the approach to compiling a digital database of fault geometry and additional attributes primarily to support seismicity monitoring at the National Observatory of Athens (NOA). A database for Greek active faults has been constructed from published fault maps in peer-reviewed journals since 1972. The standard commercial software ARC GIS has been used to design and populate the database. The fault layer was produced by on-screen digitization and is available to the scientific community in ESRI shapefile (SHP) and TXT formats in WGS84 projection. A KML file is also available to display the fault data in an Earth browser such as Google Earth. In this version of the database, we focus our attention to the active faults of the upper (Aegean + Eurasian) plate and the back-arc region of the Hellenic Arc, in general. 963 faults are included. The database is freely accessible from the Internet.